A companion to literature, film, and adaptation - Cartmell, Deborah (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2012)
This is a comprehensive collection of original essays that explore the aesthetics, economics, and mechanics of movie adaptation, from the days of silent cinema to contemporary franchise phenomena. Featuring a range of theoretical approaches, and chapters on the historical, ideological and economic aspects of adaptation, the volume reflects today's acceptance of intertextuality as a vital and progressive cultural force. Incorporates new research in adaptation studiesFeatures a chapter on the Harry Potter franchise, as well as other contemporary perspectivesShowca.
pt. I. History and contexts : from image to sound -- pt. II. Approaches -- pt. III. Genre : film, television -- pt. IV. Authors and periods -- pt. V. Beyond authors and canonical texts -- pt. VI. Case studies : adaptable and unadaptable texts.
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: Film adaptations -- History and criticism; Television adaptations -- History and criticism; English literature -- Adaptations; American literature -- Adaptations; Motion pictures and literature; Television and literature; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; American literature; English literature; Film adaptations; Motion pictures and literature; Television adaptations; Television and literature; Electronic books; Adaptations; Criticism, interpretation, etc